Ball-based learning media and children’s engagement in developing gross motor skills in early childhood education - Sovia Mas Ayu; Sulistia (CV. SPDFHarmony, 2025)
Background: Gross motor development is a fundamental aspect of early childhood education that supports children’s physical coordination, balance, and readiness for learning. Effective stimulation of gross motor skills requires learning experiences that actively engage children through meaningful movement and interaction. Learning media play an important role as mediators between children and movement-based learning activities. However, the use of ball-based learning media is often examined only in terms of motor outcomes, with limited attention to children’s engagement and human factor perspectives. Aims: This study aims to analyze the implementation of ball-based learning media in developing gross motor skills among children aged 5–6 years, with a focus on children’s engagement, coordination, and learning experiences. Method: This study employed a classroom action research design using the Kemmis and McTaggart model. The research was conducted in two cycles involving 21 children aged 5–6 years at RA Bintang Zhafira. Data were collected through observation, performance tests, and learning documentation, and analyzed using descriptive qualitative analysis supported by percentage-based developmental achievement. Results: The findings show a significant improvement in children’s gross motor skills through ball-based learning activities. Gross motor achievement increased gradually from the pre-cycle stage to the end of Cycle II, exceeding the established mastery criteria. Children demonstrated improved coordination, balance, throwing and catching accuracy, as well as higher engagement in learning activities. Conclusion: Ball-based learning media effectively support the development of gross motor skills and children’s engagement in early childhood education. The use of concrete and interactive media oriented toward human factors contributes to meaningful and holistic learning experiences.